Heterotic response in sponge gourd [Luffa cylindrical (Roem) L.] (Indian Journal of Arid Horticulture, 2025)
Sponge gourd [Luffa cylindrica (Roem) L.] plays a significant role in the diet of human nutrition, especially in tropical countries. It is one of most popular vegetable during summer and rainy seasons in northern India. Sponge gourd is a monoecious crop and cross pollination is a general rule which facilitates exploration of heterosis. It exhibits high heterosis (Mole et al., 2001 and Ram et. al. 2004) which suggest a great scope of improvement through heterosis breeding. Today hybrids are gaining popularity due to their carliness, high productivity, better quality and adaptation to environmental condition. Realizing the importance of hybrid vigour, an investigation was undertaken to identify potential parental combinations in order to have superior hybrids with good yield and quality traits. Fifteen diverse sponge gourd inbreds viz., VRSG- 1.
Keywords: heterosis; Sponge gourd; hybrids; monoecious; pollination